The Development of Interactive Media on Hindu Religious Education Subject For The Second Semester of VIII Grade Learners at SMP Negeri 1 Ubud - Eka Santika Putra, I Wayan; Suarnaya, I Putu (International Journal of Multidisciplinary Sciences, 2023)
Multimedia technology has a very diverse function, especially in the world of education. In learning, teachers are expected to have skills in mastering the material, teaching strategies and teaching models that are in accordance with the classroom environment and innovative and varied learning approaches.  Therefore, teachers should pay attention to matters related to teaching skills according to the needs of students in the classroom. One of the subjects that requires a comprehensive approach in the learning process is the subject of Hindu Religious Education. The use of media in the learning process is to facilitate interaction between teachers and students which aims to help students learn effectively. The ADDIE learning model in the learning process does not only use in-class meetings, but is used to incorporate out-of-class learning and technology into the subject matter. So as to increase students' appreciation of Hindu religious education subjects and independent learning carried out by students at home. The stages of the ADDIE learning process are starting from the stages of analysis, design, development, implementation and evaluation. This study aims to determine the development of multimedia technology that is effectively and efficiently applied to the subjects of Hindu Religious Education. The data collection methods used are test methods and questionnaires, with then supporting instruments in the form of interviews and video recordings. The data analysis used in this study is qualitative descriptive analysis techniques, quantitative descriptive statistical analysis, inferential statistical analysis. The results showed the development of interactive multimedia developed effectively to improve Hindu learning outcomes.